Extension Approaches Adopted by the Agri-allied Sector Departments of Karnataka State - Kareem, Mohd. Abdul; Phand, Shahaji; Borade, Madhusudan (Journal of Agricultural Extension Management, 2019)
The extension approaches followed by different extension organizations have resulted into wider spread of modern technologies and increase in agricultural production. However, in the agri-allied sector these extension approaches are not fully adopted due to several reasons.It has been seen that majority (85%) of the animal husbandry officers in Karnataka visited the farmers field daily, followed by sericulture officers (60%) and 50 per cent of horticulture officers and fisheries officers. Nearly 45 per cent of the horticulture officers, 40 per cent of the sericulture and fisheries officers and 10 per cent of the animal husbandry officers were involved in formation of farmer groups. General Extension Approach was the most popular among the agri-allied sector officers. It has been noticed that 90 per cent of horticulture officers, 85 per cent of animal husbandry officers and 70 per cent of the sericulture and fisheries officers were aware of the Agricultural Technology Management Agency (ATMA). However most of them; viz., 70 per cent of the sericulture officers,Â 50 per cent of the fisheries officers, 65 per cent of both animal husbandry and horticulture officers had no knowledge about the key functions of ATMA. Cent per cent of all the department officers in Karnataka stated that extension services were not system based and not converged with the other line departments. None of the officers recommended any farming systems to the farmers. Participatory approach and ICT approach were not much practiced by the allied sector officers as only 25 per cent were affirmative about the details of the participatory approach. Commodity approach and project approach of extension were least popular with the agri-allied officers of Karnataka State. Thus, it can be concluded that to promote adoption of other extension approaches among the agri-allied department officers, capacity building through induction training and refresher training programs on extension management aspects and well defined job chart inclusive of frequent field visits is the need of the hour for Karnataka State.